Comparative Study of Transcriptome Profiles of Mouse Livers and Skins Infected by Fork-Tailed or Non-Fork-Tailed Schistosoma japonicum - Yang, Yan; He, Jun-Jun; Hu, Shuang; Chang, Hua; Xiang, Xun; Yang, Jian-Fa; Zou, Feng-Cai (Frontiers in Microbiology, 2017)
Schistosoma japonicum (S. japonicum) is a worldwide spread pathogen which penetrates host skin and then induces several diseases in infected host, such as fibrosis, formation of granulomas, hepatocirrhosis and hepatomegaly. In present study, for the first time, transcriptomic profiles of mouse livers and skins infected by fork-tailed S. japonicum cercaria or non-fork-tailed S. japonicum cercaria were analyzed by using RNA-seq. The present findings demonstrated that transcriptomic landscapes of livers and skins infected by fork-tailed S. japonicum cercaria or non-fork-tailed S. japonicum cercaria were different. S. japonicum has great influence on hepatic metabolic processes. Fork-tailed S. japonicum cercaria upregulated hepatic metabolic processes, while non-fork-tailed S. japonicum cercaria downregulated hepatic metabolic processes. For the metabolism process or the metabolism enzyme expressional change, the pharmacokinetics of host could be changed during S. japonicum infection, regardless the biotypes of S. japonicum cercariae. The changes of infected skins focused on upregulation of immune response. During the S. japonicum skin infection period, fork-tailed S. japonicum cercaria infection induced stronger immune response comparing with that immune response triggered by non-fork-tailed S. japonicum cercaria. The ranscription factor enrichment analysis showed that Irf7, Stat1 and Stat2 could play important roles in gene regulation during fork-tailed S. japonicum cercaria infection.